Recife’s beachrocks: an example of a geosite with high geotourism relevance in northeastern Brazil - Barreto, A. M. F. (2011)
In Recife, northeastern Brazil, beachrocks were formed after the last marine transgression and have today a scientific, educational, historical and tourism relevance, constituting a geosite. This work aims at the promotion of this geosite interpretation, its conservation and proper use by different types of public.